Polyphenol components in black chokeberry (Aronia melanocarpa) as clinically proven diseases control factors—an overview - Ningxuan Gao; Chi Shu; Yuehua Wang; Jinlong Tian; Yuxi Lang; Chenyu Jin; Xingyue Cui; Hanqian Jiang; Shi’an Liu; Zhiying Li; Wei Chen; Hao Xu; et al. (Food Science and Human Wellness)
The black chokeberry is rich in polyphenols, including flavonoids with anthocyanins, flavanols and f lavonols as the main components and a variety of phenolic acids represented by chlorogenic acid. Because of these polyphenols, black chokeberry has the effect of preventing and adjuvant therapy diseases. This study summarized the current research results on the types and contents of functional components in black chokeberry, and analyzed their digestion, absorption and metabolism in human body. On this basis, the disease control functions that have been proved effective in clinical research were reviewed and analyzed. These studies showed that black chokeberry have good prevention and adjuvant therapy effects on hyperlipidemia,hypertension, diabetes and inflammation. Because there are different functional components in black chokeberry, its prevention and treatment of the same disease can come from multiple pathways, which provides a more reliable effectiveness for the disease control of different populations.